Wandering in the great forests of Borneo travels and researches of a naturalist in Sarawak - Beccari, Odoardo 1843-1920 (Crescent News Sdn Bhd, 2015)
First published in Italian 1902, this book is a vivid record of the diversity of the tropical plant life of Borneo as seen through the eyes of a dedicated botanist.